2002
DOI: 10.1055/s-2002-32952
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic Studies Toward Tetrodecamycin: An Efficient Approach to the Core Structure of the Antibiotic

Abstract: S y n t h e t i c S t u d i e s t o w a r d T e t r o d e c a m y c i nAbstract: An efficient synthetic pathway to the core structure 5 of the polyketide antibiotic tetrodecamycin (1a) has been developed. Our approach features the acid-catalyzed cyclization of a tert-butyldimethylsilyl protected methyl a-(g-hydroxyacyl) tetronate, leading to the novel tricyclic ring skeleton exhibited by 5. An insight into the mechanism of this key ring closure step has been gained. Furthermore an alternative pathway to this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Moreover, the quaternary carbons are located at C 7 and C 13 [89]. The imposing structure and optical medicinal importance of this molecule have attracted a great deal of attention from the other researchers since the disclosure of the structure [90][91][92][93][94][95], although the total synthesis had not been reported until our synthesis [96].…”
Section: Total Synthesis Of (à)-Tetrodecamycinmentioning
confidence: 99%
“…Moreover, the quaternary carbons are located at C 7 and C 13 [89]. The imposing structure and optical medicinal importance of this molecule have attracted a great deal of attention from the other researchers since the disclosure of the structure [90][91][92][93][94][95], although the total synthesis had not been reported until our synthesis [96].…”
Section: Total Synthesis Of (à)-Tetrodecamycinmentioning
confidence: 99%
“…An initial retrosynthetic analysis of tetrodecamycin suggested that this structure could be synthesized from a decalin derivative and a tetronic acid derivative, inspiring the first efforts toward the synthesis of tetrodecamycin. 43 This strategy made two features of the molecule important targets in these early synthetic studies: the asymmetric synthesis of the novel seven-membered ring core, [43][44][45] and the synthesis of the decalin portion of the molecule. [46][47][48] These efforts culminated with the successful total synthesis of tetrodecamycin 2006 through a pinacol cyclization mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…enolates have proved to be a very good option to achieve C-3 acylation. Thus, these anolates have been used to build the tricycle core of the novel poliketide antibiotic tetrodecamycin (52)60,61 (Scheme 22). PhBCl 2 , i-Pr 2 NEt, CH 2 Cl 2 , -78ºC, 2) -78ºC to RT, 86%; (ii) IBX, DMSO, RT, 91%; (iii) cat.…”
mentioning
confidence: 99%